Clinical benefits of Bifidobacterium infantis YLGB-1496 in modulating gut microbiota and immunity in young children - Uma Mageswary, Mageswaran; Li, Pin; Richmond, Rocky Vester; Azianey, Yusof; Abd Hamid, Intan Juliana; Taib, Fahisham; Liong, Min-Tze; Ali, Adli; Tan, Joo Shun; Zhang, Yumei (Frontiers in Nutrition, 2026)
IntroductionThe early-life gut microbiota is critical for immune development and long-term health, and plays an essential role in the digestion and metabolism of dietary components, including human milk oligosaccharides (HMOs). Probiotic supplementation is a promising strategy to modulate this ecosystem and prevent common childhood infectious illnesses, though strain-specific effects require further investigation.MethodThis 12-week, double-blind, randomized, placebo-controlled trial evaluated the efficacy of Bifidobacterium infantis YLGB-1496 (1 × 1010 CFU/day) in 119 healthy preschool children. Participants were assessed for respiratory and gastrointestinal (GI) illness incidence, inflammatory biomarkers (fecal IgA, cytokines, calprotectin; salivary cortisol), and gut microbiota composition via 16S rRNA sequencing.ResultProbiotic supplementation significantly reduced the incidence of respiratory problems as compared to the placebo group (Week 12: 15.0 vs. 42.4%, p < 0.001) and diarrhea (Week 6: 18.3 vs. 44.1%, p = 0.002), alongside fewer clinical visits and antibiotic prescriptions (p < 0.01 for all). Immunologically, the probiotic group exhibited a favorable anti-inflammatory profile with reduced levels of fecal IFN-γ, IL-1β, and calprotectin, and a trend toward increased fecal IgA over time as compared to the placebo group. Microbiota analysis revealed that the probiotic did not induce major restructuring but provided ecological stability, preventing the and preserving beneficial SCFA producing genera that declined in the placebo group (p < 0.05).ConclusionB. infantis YLGB-1496 is an effective probiotic that reduces the burden of common childhood infectious illnesses by fine-tuning immune responses and enhancing the resilience of the gut microbial ecosystem, rather than through drastic compositional changes. These findings support its use as a safe nutritional intervention for promoting pediatric health.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT05794815?term=NCT05794815&rank=1, identifier number: NCT05794815.